Pengembangan dan validasi bahan ajar multimedia interaktif materi hukum kirchhoff menggunakan adobe flash cs6 - Kharen Riz Lambar Wati; I Wayan Distrik; I Dewa Putu Nyeneng; Abdurrahman Abdurrahman (Universitas Sultan Ageng Tirtayasa, 2020)
Graduates' standards of competency and content in the national curriculum explain the principle of learning should be done anywhere. Technology was using to improve the effectiveness and efficiency of learning. The education world still needs teaching materials that support the learning process. The purpose of this research was to produce a viable interactive multimedia product. The multimedia eligibility criteria were reviewed from the content and construct validation test, practicality test, and effectiveness test. This research was development research carried out in four main stages, namely preliminary studies, planning and development, field testing, and dissemination. The multimedia component consists of core competencies, essential competencies, text, sound, images, animation, material explaining in detail, and practice questions that could be adjusted to students' needs. The results showed that interactive multimedia teaching materials were valid in terms of content and constructed. They practically used as well as a solution to the impracticality of learning principles, as well as effectively increasing students' cognitive abilities.